Design and development of FTMSK alumni information repository / Herojer Asoon - Asoon, Herojer (2006)
FTMSK Alumni Repository System is an information system that will complement the FTMSK portal. For alumni members, students and the faculty itself, the proposed system has a good implication in the future. Thus, three objectives emerge, that are to find requirements, design a solution and apply taxonomy in the development of FTMSK Alumni Repository System. With the data gathered through readings, observations, and feedbacks from users, prototyping approach was chosen as it is suitable to build information system in limited time. Approximately four months was used to build the prototype into an acceptable product and it is able to do the basic functions requested. The taxonomy incorporated into the system through profiling supports the information system in several areas even so, the; prototype still needs further improvements.